2017
DOI: 10.1136/esmoopen-2017-000238
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intra-arterial hepatic chemotherapy with doxorubicin-loaded nanoparticles in hepatocellular carcinoma

Abstract: BackgroundDoxorubicin Transdrug (DT), a nanoformulation of doxorubicin, was demonstrated to overcome the chemoresistance of hepatocellular carcinoma (HCC) in preclinical models. Its efficacy and safety were thus investigated in phase I and randomised phase II trials in unresectable HCC.Patients and methodsPhase I was a single dose of DT through the hepatic intra-arterial (HIA) route, dose-escalating 3+3 trial, evaluating five-dose levels from 10 to 40 mg/m2 with maximal tolerated dose (MTD) as primary endpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Consistent with previously published data, clinically significant (observed in at least 10% of patients) drug related treatmentemergent adverse events of any grade attributable to doxorubicin were mostly asthenia, nausea, vomiting, and neutropenia, whereas thrombo cytopenia (probably due to gemcitabine) and par aesthesia (probably due to oxaliplatin) were observed in the control group. Although acute respiratory distress syndrome occurred in some patients due to intrahepatic arterial injection of doxorubicinloaded nanoparticles in the phase 1-2 trial, 24 no clinically significant pulmonary treatmentemergent adverse events were observed after 6 h of intravenous perfusion in RELIVE. Headache was more prevalent in the patients who received the nanoparticleloaded doxorubicin, which might be specific to the nanoformu lation, since this is not commonly reported with free doxorubicin, but is reported with other forms of nano formulation of doxorubicin such as liposomal doxo rubicin.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Consistent with previously published data, clinically significant (observed in at least 10% of patients) drug related treatmentemergent adverse events of any grade attributable to doxorubicin were mostly asthenia, nausea, vomiting, and neutropenia, whereas thrombo cytopenia (probably due to gemcitabine) and par aesthesia (probably due to oxaliplatin) were observed in the control group. Although acute respiratory distress syndrome occurred in some patients due to intrahepatic arterial injection of doxorubicinloaded nanoparticles in the phase 1-2 trial, 24 no clinically significant pulmonary treatmentemergent adverse events were observed after 6 h of intravenous perfusion in RELIVE. Headache was more prevalent in the patients who received the nanoparticleloaded doxorubicin, which might be specific to the nanoformu lation, since this is not commonly reported with free doxorubicin, but is reported with other forms of nano formulation of doxorubicin such as liposomal doxo rubicin.…”
Section: Discussionmentioning
confidence: 95%
“…Treatment could be continued beyond progression at the decision of the principal investigator. To prevent the occurrence of acute respiratory adverse events that we observed in our phase 1-2 trial, 24 perfusion of doxorubicinloaded nanoparticles was done over 6 h intravenously with safety measures (premedication with methyl prednisolone 32 mg orally and one antihistamine drug given 24 h and 1 h before perfusion and 24 h after perfusion). Respiratory symptoms and oxygen saturation were continuously monitored during the 6 h of perfusion: in case of dyspnoea or oxygen saturation decrease from 95% or more to 93% or less, the infusion rate was reduced by half (to a 12 h infusion) without changing the total dose; in case of persistence of dyspnoea beyond 1 h or oxygen saturation decrease to 90% or less, perfusion was immediately and definitively stopped.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PET images were performed before (at the 13th day) and after three MHT applications (at the 22nd day), as depicted in Figure 10, using a small animal equipment Triumph ® II preclinical scanner (Gamma Medica-Ideas, Nortridge, CA, USA). 18 F-FDG (38)(39)(40) was injected in the penile vein and after 45 min, the animal was posionited with the brain in the center of the field of view. Image was acquired for 30 min and reconstructed using OSEM 3D algoritm, 20 interactions, and 4 subgroups.…”
Section: Evaluation Of Mht Therapeutic Effect By 18 F-fdg-petmentioning
confidence: 99%
“…MHT therapy outcome evaluation has been reported by different approaches using conventional techniques as follows: trypan blue [19,32,33], MTT [19,[34][35][36], tunnel assay [32], live/dead assay [37,38], and Western blot [32] that in most cases have limitations for longitudinal analysis.…”
Section: Introductionmentioning
confidence: 99%